Development of Interactive Computer Based Media for Learning Mathematics on Greatest Common Divisor (GCD) and Least Common Multiple (LCM) Topics - Jalinus, Jalinus; Alim, Jesi Alexander (Proceedings of the UR International Conference on Educational Sciences, 2018)
The purpose of research is to make an interactive computer based media for learning mathematics onGCD and LCM topics which is can be used by the teachers and students because this interactive computer based media is using the fun animation corresponded to the thinking stage of the elementary school student is on concrete stage. This research is development research with these following steps : 1. Analysis, including a) interview with fourth grade elementary school teacher about learning of mathematics, b) analyze the syllabus of the fourth grade mathematics subject, c) analyze the book text of the matchematics, d) review the literature of teaching materials. 2. prototype phase, including a) validation, b) practicality , doing a trial to Babussalam Elementary School Pekanbaru. 3. Assesment, evaluate if the prototype can be used as expected and effective to increase the quality of learning. The results show that the interactive computer based media for learning mathematic on GCD and LCM topics is valid. The trials to the fourth grade students of Babussalam Elementary School result show that the interactive computer based media for learning mathematics on GCD and LCM topics is practice, proven by the description and the data analysis can be conclude that the learning materials is effective to make the students learning activities and make the students learning independently and fun.